Pulmonary Embolism in Deceivingly Stable Patients with High Thrombus Load—When Is Stable Really Safe? - Lepper, Philipp M.; Wilkens, Heinrike; Link, Andreas; Bals, Robert; Schäfers, Hans-Joachim (The Thoracic and Cardiovascular Surgeon, 2014)
The definitive treatment of hemodynamically stable patients with pulmonary embolism and echocardiographically proven moderate to severe right ventricular dysfunction is unclear. We discuss the cases of a 45-year-old woman and a 62-year-old man that fulfilled the above criteria, but had a high risk for adverse events. Although both patients were treated according to current guidelines, one underwent successful surgical embolectomy the same day and the other was resuscitated a few days later. Surgery is an alternative for carefully selected patients with mild right ventricular dysfunction, but a high risk for adverse events that would otherwise be treated the same way as low- to moderate-risk patients.
Keywords: pulmonary embolectomy; pulmonary embolism; right ventricular dysfunction; echocardiography